Teaching Skills and Views of Pre-Service Biology Teachers on Response to The Instructional Video With Scientific Approach in Cooperative Learning - Susantini, Endang; Faizah, Ulfi; Prastiwi, Muji Sri (Proceeding of International Conference on Teacher Training and Education, 2016)
Essential teaching skills of pre-service teachers, including scientific approach teaching in which become primary goal in science education, are often developed through modeling. This study utilized an instructional video in biology that showed scientific approach teaching in cooperative learning model. The purpose of this study was (1) to describe the teaching skills of pre-service biology teachers after a modeling session which used the instructional video using scientific approach in cooperative learning, and (2) to describe the views of those pre-service teachers in response to the learning process involving the instructional video. The study involved 11 pre-service teachers in Biology Education program, The State University of Surabaya, Indonesia. The pre-service teachers were asked to conduct teaching simulations according to the video they had observed with different biology topics. Results showed that the instructional video was effective in training pre-service teachers to implement scientific approach in their own cooperative learning. In addition, the pre-service teachers showed positive responses towards the video modeling. Educational implication of this study implies that the instructional video is able to train teaching skills of pre-service teachers.